2016
DOI: 10.1371/journal.pone.0154917
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Double-Lumen Extension Tube on Drug Delivery: Examples of Isosorbide Dinitrate and Diazepam

Abstract: PurposePlastic materials such as polyurethane (PUR), polyethylene (PE), polypropylene (PP) and polyvinyl chloride (PVC) are widely used in double-lumen extension tubing. The purposes of our study were to 1) compare in vitro drug delivery through the double extension tubes available on the market 2) assess the plastic properties of PUR in infusion devices and their impact on drug delivery.MethodsThe study compared eight double-lumen extension tubes in PUR, co-extruded (PE/PVC) plastic and plasticised PVC from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…A loss of isosorbide dinitrate, tacrolimus, diazepam, amiodarone, insulin has been observed during infusions via PVC tubings. [2][3][4][5][6][7][8][9] These losses of API by sorption can require an adjustment of the dose administered, based on the expected biological effect of the drug. Sometimes, rinsing the tubing by the drug before its administration is a possible way to limit these interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A loss of isosorbide dinitrate, tacrolimus, diazepam, amiodarone, insulin has been observed during infusions via PVC tubings. [2][3][4][5][6][7][8][9] These losses of API by sorption can require an adjustment of the dose administered, based on the expected biological effect of the drug. Sometimes, rinsing the tubing by the drug before its administration is a possible way to limit these interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Sorption generally occurs in the early phase of infusion, and the pattern is followed by a convection-interfacial resistance-diffusion model 7 . Diazepam sorption results are comparable to the double-lumen extension tube model 17 when the initial drug concentration is considered before delivery. Therefore, sampling time points can be modified so that sorption evaluation takes less time.…”
mentioning
confidence: 63%
“…In a recent study, Foinard et al . 2 highlighted that thermoplastic PU were more prone to absorption of diazepam and isosorbide dinitrate than thermosetting PU. The polyurethane used in this study was of thermoplastic nature, and also showed a high tendency to promote diazepam sorption, which is coherent with their results.…”
Section: Discussionmentioning
confidence: 99%
“…It can affect drug solutions by releasing compounds into the infusate or by retaining the drug (sorption) thus potentially affecting infusion safety and effectiveness. Sorption phenomena can cause a loss of active pharmaceutical ingredient (API) 1,2 or protective excipients 3 and are mediated by different physicochemical parameters/properties 4–6 that are still incorrectly evaluated. The phenomena can be detailed in two steps: adsorption then absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation